Flexural and compression behavior analysis of hybrid sandwich composites with nano silicon particles in low-velocity impact analysis - Mani, Megavannan; Thiyagu, M; Kumar Krishnan, Pradeep (Materials today : proceedings, 2023)
•Epoxy LY556 and hardener HY951 were kept at 10:1.•Bidirectional fibers stacked with the 01K/01C/01G/PUR/01G/01C/0 K.•Hand layup was used to create the sandwich composite panels.•24.2% of tensile strength, 23.81% of shear strength was significantly improved.•12.54% of torsional strength was higher than control sprcimen. Sandwich polymers are frequently used in a wide range of technical applications due to their lightweight construction and excellent rigidity. The present investigation aims to assess and investigate the flexural and compressive strengths of sandwich polymer composite panels in Low-velocity impact (LVI) analysis, as well as to compare the properties of sandwich composite structures with and without silica nanoparticles. The hand layup method is employed to fabricate sandwich composite structures made of silica nanocomposite. These hybrid sandwich panels combine kevlar, carbon, glass, and epoxy polymer structures with polyurethane (PUR) foam. Using the inventive stacking sequence method, these lamination structures (01K/01C/01G/PUR/01G/01C/01K), were layered, and silica nanoparticles were added at weight percentages of 0, 2, and 4. As a result, improved hybrid sandwich polymer panels were produced. The combination of these panels with wt. 4% silicon nanoparticles (SiNPs) in the composite lamination structure exhibits 23.61% greater flexural and 27.01% compression strengths and higher yield strengths when compared to the hybrid sandwich panels without a silica nanocomposite lamination matrix.